063 Actinomyces cavernous sinus infection: a case and systematic literature review. Issue 6 (24th May 2018) - Lubomski, Michal; Dalgliesh, James; Lee, Kenneth; Damodaran, Omprakash; McKew, Genevieve; Reddel, Stephen
Abstract : Case: We report an unusual case of a 63 year old man who developed progressive right-sided exophthalmos, painful ophthalmoplegia, headaches and fevers with worsening depression over a two-month period, subsequently identified as an Actinomyces cavernous sinus (CS) infection. Preliminary diagnoses included giant cell arteritis then Tolosa-Hunt syndrome, with a transient response to steroids. Investigations showed a bland CSF and highly metabolically active brain FDG-PET suggesting lymphoma. Biopsy of the mass demonstrated gram-positive filamentous bacteria with Actinomyces -like colonies with sulphur granules. Actinomyces CS infections are rare. They often mimic non-infectious etiologies including other inflammatory and infiltrative conditions, vascular and neoplastic causes, particularly lymphoma. Conclusion: Clinicians should consider infective CS syndromes in fluctuating painful ophthalmoplegias with poor response to steroids. In our view, "Tolosa-Hunt" should not be used as a diagnosis but merely used as a descriptor for syndromes that resolve with corticosteroids in the absence of a more precise diagnosis.